FRI0286 High-Dose Intravenous Pulse Methotrexate in Patients with Eosinophilic Fasciitis: An Open Prospective Study. (15th July 2016) - Mertens, J.S.; Zweers, M.C.; Kievit, W.; Knaapen, H.K.; Gerritsen, M.; Radstake, T.R.; van den Hoogen, F.H.; Creemers, M.C.; Jong, E.M.
Abstract : Background: Eosinophilic Fasciitis is a rare scleroderma-like connective tissue disorder. No treatment has shown to be effective in randomized trials. The treatment most often reported is combination of moderate to high-dose glucocorticoids (1–1, 5mg/kg/day) with weekly methotrexate (MTX), up to 25mg, but often with disappointing results. 1, 2 Objectives: To examine the effect and safety of monthly intravenous (IV) high dose MTX in patients wtih eosinophilic fasciits. Methods: Patients with biopsy proven eosinophilic fasciits and progression of skin involvement, who were either treatment naïve or not responsive to glucocorticoids and MTX were included in this open prospective study. Treatment consisted of IV pulse MTX 4 mg/kg/month for 6 doses in 5 consecutive months. Twenty-four hours after the administration of MTX, 5mg folinic acid was orally taken every six hours, to a maximum of 25 mg/day. Patients were evaluated monthly, prior to every infusion. Primary outcome measure was the absolute improvement at month 5 compared to baseline of the modified skin score (mSS), according to Zachariae. 3 Secondary outcome measures were durometer scores, Range of Motion (RoM) and Visual Analogue Scale (VAS) scores for disease activity by physician and patient and Short-Form-36. Results: Between 2006 and 2009, 12 patients were included and the median monthly MTX dose was 288mg (range 252–336). The median mSS improved from 17.5 [range 8.0–24.0] at baseline to 8.5 [range 1.0–20.0] at 5 months (p=0.001) (Fig 1 ). Compared to baseline, secondary outcome measures improved significantly, except for durometer scores and the range of motion of the elbows. There was no significant difference in skin improvement between the treatment naïve and non-naïve patients (p=0.968). After the last dose of IV MTX, EF flared in six patients after a median of 2 months (range 2–5). A second cycle with IV MTX (3 pulses) was administered to these 6 patients, with a favourable response in all patients. One patient was withdrawn due to increased liver enzymes (2 – times upper limit of normal) after 5 administrations, which normalized after MTX withdrawal. Gastro-intestinal symptoms were present in the majority of the patients (n=9), but manageable with anti-emetics. Conclusions: High dose IV MTX could be an effective and safe treatment option in patients with eosinophilic fasciitis. References: Lebeaux D, Frances C, Barete S, et al. Eosinophilic fasciitis (Shulman disease): new insights into the therapeutic management from a series of 34 patients. Rheumatology. 2012; 51: 557–61. Wright NA, Mazori DR, Patel M, et al. Epidemiology and Treatment of Eosinophilic Fasciitis: An Analysis of 63 Patients From 3 Tertiary Care Centers. JAMA dermatology. 2016; 152: 97–9. Zachariae H, Bjerring P, Halkier-Sorensen L, et al. Skin scoring in systemic sclerosis: a modification–relations to subtypes and the aminoterminal propeptide of type III procollagen (PIIINP). Acta dermato-venereologica. 1994;74: 444–6. Disclosure of Interest: None declared